1966
DOI: 10.1042/bj0990179
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the sub-units of α-crystallin

Abstract: 1. A new procedure is described for the purification of alpha-crystallin, including: preparative zone electrophoresis, density-gradient centrifugation and gel filtration. The total amino acid composition of highly purified samples prepared according to this procedure has been determined. 2. Evidence is presented for the presence of intermediates in the urea-induced splitting of alpha-crystallin into sub-units. A possible mechanism for this splitting is proposed. 3. The recombination of sub-units has been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1967
1967
1981
1981

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The mean molecular weight of the subunit as calculated by approach to equilibrium methods is about 24,000 (Bont et al 1962, Wisse et al 1966. The mean molecular weight of the subunit as calculated by approach to equilibrium methods is about 24,000 (Bont et al 1962, Wisse et al 1966.…”
Section: Iiiscussionmentioning
confidence: 99%
“…The mean molecular weight of the subunit as calculated by approach to equilibrium methods is about 24,000 (Bont et al 1962, Wisse et al 1966. The mean molecular weight of the subunit as calculated by approach to equilibrium methods is about 24,000 (Bont et al 1962, Wisse et al 1966.…”
Section: Iiiscussionmentioning
confidence: 99%
“…A subunit structure occurs in the oc-crystallins of bovine lens (Wisse, Zweers, Jongkind, Bont & Bloemendal, 1966) and in the ,-crystallins (also called FISC or &-crystallins) of the chick (Clayton & Truman, 1967). It also appears probable that the y-crystallins (known also as /8-or 'long line' crystallins) of the chick are composed of subunits.…”
Section: Pmentioning
confidence: 99%
“…Bovine ac-crystallin contains 1 cysteine residue/20 000 g. of protein (Thomann, 1959;Wisse et al 1966) and partial acid hydrolysis of the carboxymethylated protein gives Ser-CMOys (Waley, 1965a). This is a characteristic of bovine a-crystallin shared by human a-crystallin and by bovine and human albuminoid.…”
Section: Discussionmentioning
confidence: 99%
“…Bjork (1964) found that the early-peak protein aggregated (after the urea had been removed by dialysis) and he obtained S20.,, 13*2s, a value comparable with those obtained from the late-peak proteins. Moreover, the early-peak proteins represent the slowest bands seen on electrophoresis of a-crystallin in polyacrylamide gel in 7M-urea (Bjork, 1964;Wisse et al 1966); these bands are present when extensively purified a-crystallin is used, and Wisse et al (1966) concluded that the complexity of the electrophoretic pattern was not due to impurities in acrystallin. The amino acid composition ofthe earlypeak protein (Bjork, 1964;Spector, 1965) is consistent with this conclusion: proline and phenylalanine are relatively abundant, glycine and tyrosine are relatively scarce; these are features that distinguish a-crystallin from fi-crystallin and y-crystallin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation